Environmental impact assessment : Indo-Australian perspective / edited by Behnam Ta'i, Peter Murphy [and] P.S. Rana - Ta'i, Behnam (ed.) (New Delhi, 2007)
Environmental issues today are as diverse as they are serious. The daily life and economic base of developing regions largely depend upon natural resources, such as forests, soil and water. Strangely many of the efforts to combat poverty, hunger, disease and illiteracy inevitably result in the destruction of nature. Such depletion of natural resources cause deterioration of living conditions, which is aggravated by the effects of population growth and urbanization. In the midst of socio-economic globalization, all these problems are inter-connected and environmental damage is becoming even more complex and serious.
Keywords: Environment